Book Reviews (Journal of Finance, 1982)
Book reviewed in this article: Risk and Capital Adequacy in Commercial Banks . Edited by SHERMAN J. MAISEL Essentials of Managerial Finance: Principles and Practice. By STEVEN E. BOLTEN and ROBERT L. Money and Banking . By TYRONE BLACK and DONNIE DANIEL Financial Institutions, Markets, and Money . By DAVID S. KIDWELL and RICHARD L. PETERSON Wall Street in the American Novel . By WAYNE W. WESTBROOK